Pengaruh E-WOM dan E-Servqual terhadap Minat Beli Peran Mediasi Kepercayaan Merek - Agustina Agustina; Suhada Suhada (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This investigation examines how electronic word-of-mouth (e-WOM) and electronic service quality (e-servqual) influence purchase intention through brand trust as a mediating variable, focusing on Rumah Undangan.id, a digital invitation SME on Shopee. Using Social Exchange Theory (SET), the research explores how digital interactions and online service quality create perceived exchange value, strengthen consumer trust, and drive purchase intention. A quantitative approach with purposive sampling was employed, collecting data from 196 respondents who purchased digital invitation products. Data was gathered via online forms and analyzed using SEM-PLS methodology. Findings reveal that e-WOM significantly and positively affects both brand trust and purchase intention. Similarly, e-servqual significantly influences trust and purchase intention. Brand trust positively impacts buyer motivation and mediates the relationship between e-WOM, e-servqual, and purchase intention. Study limitations include its focus on a single MSME brand, limiting generalizability, and reliance on respondent perceptions without considering other external variables. The research contributes theoretically by strengthening SET application in digital marketing contexts through integrating e-WOM, e-servqual, and brand trust. Practically, it offers insights for digital-based MSMEs to enhance consumer purchase intention by managing positive online reviews and improving e-servqual to build sustainable brand trust. Keywords: e-wom, e-servqual, brand trust, purchase intention, SET